Administrative and Legal Liability of Entities Providing Cosmetological Services in Ukraine - А. I. Sadovenko (Bulletin of Kharkiv National University of Internal Affairs)
The problematic issue of legislative regulation of cosmetological activities in Ukraine, which concerns the subjects of providing cosmetological services and liability for the violation of their professional duties, has been studied. The author has offered own definition of the term of “administrative liability in the field of providing cosmetological services”. It has been established that administrative liability in the studied area arises on the basis of the commission of a tort by a specific subject. The classification of administrative liability in the field of providing cosmetological services, depending on the subject of the tort, has been accomplished. The author has offered to consider a person who provides assistance aimed at improving a person’s appearance, treatment or masking the defects in appearance in order to change the psychophysical condition of a person and meet his aesthetic needs as a subject of providing cosmetological services. It has been determined that the improvement of administrative legislation in the field of providing cosmetological services in Ukraine should be understood as the development of theoretical and practical areas of capacity building for further development of this phenomenon and the settlement of disputes that arise by revising, repealing or creating regulatory acts in this sphere. The necessity of codification of the legislation on the provision of cosmetological services has been substantiated. The existing theoretical provisions have been summarized and a new solution to the scientific problem of improving the administrative and legal liability of the entities providing cosmetological services in Ukraine has been suggested. It has been clarified that it is important to establish the basic requirements for the procedural aspects of providing medical and cosmetological services, for updating administrative legislation in this part, as well as the definition and consolidation of administrative and legal liability of entities providing cosmetological services in Ukraine.